PERANAN ELIT DALAM REKONSTRUKSI BUDAYA LOKAL “INGOT-INGOT” DI DESA PANRIBUAN KABUPATEN SIMALUNGUN - Plaza Sembiring, Albret Metro; Erawan, I Ketut Putra; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2017)
ABSTRACT The research was based on the strong position of a group of elite in a village in Karo Tribe called